Character Education Strategies Through the Islamic Personal Development Program at It Annida Lubuklinggau Junior High School - Tobel Nursebsa; Zuhri Zuhri; Muslih Hidayat; Moh In'ami (Pascasarjana UIN ANTASARI Banjarmasin, 2022)
The purpose of the study is to determine the strategy of character education through the Islamic personal development (BPI) program in shaping the personality of students. The research approach is skin research. The effectiveness of the research used is phenomenology which examines how the implementation of the Islamic personal development program. The concept of purposeful sampling is used in qualitative research where the researcher selects individuals and research locations for a study because these choices can provide information to answer the researcher's problems. The samples and participants of the study were principals, vice principals, BPI chief coordinators, and BPI teachers. Data collection with interviews, observations, and documentation. The results showed that SMP IT Annida Lubuklinggau has carried out a character formation strategy for students by making habituation and exemplary program, this is a good character building so that students are more religious and always apply discipline. SMP IT Annida Lubuklinggau applies character education based on good habituation. Starting from coming to school to returning home from school, even when at home, it is still implemented. The Islamic personal development program evaluates the activities of students daily starting with their worship, attitudes, and other activities that have been received by students from the results of BPI activities.